2014
DOI: 10.1111/jdi.12187
|View full text |Cite|
|
Sign up to set email alerts
|

Postprandial C‐peptide to glucose ratio as a predictor of β‐cell function and its usefulness for staged management of type 2 diabetes

Abstract: Aims/IntroductionType 2 diabetes is characterized by progressive deterioration of β‐cell function. Recently, it was suggested that the C‐peptide‐to‐glucose ratio after oral glucose ingestion is a better predictor of β‐cell mass than that during fasting. We investigated whether postprandial C‐peptide‐to‐glucose ratio (PCGR) reflects β‐cell function, and its clinical application for management of type 2 diabetes.Materials and MethodsWe carried out a two‐step retrospective study of 919 Korean participants with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Pancreatic beta cell function and insulin sensitivity were assessed by using the following indices [9]: Homeostatic model assessment of pancreatic β-cell function (HOMA-β) =[(basal insulin [pM]×0.48)/(basal glucose [mM]-3.5)]; HOMA-IR=[(basal insulin [pM] × glucose [mM]) / 156.3]; C-peptide increment (ΔC-peptide=[stimulated C-peptide (pmol/mL)-basal C-peptide (pmol/mL)]; and insulin increment (Δinsulin=[stimulated insulin (pmol/L)-basal insulin (pmol/L)]. PCGR was defined as follows [10]: [(stimulated C-peptide [ng/mL]/stimulated glucose [mg/dL])×100]. The eGFR was derived from the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine-based equation [11].…”
Section: Methodsmentioning
confidence: 99%
“…Pancreatic beta cell function and insulin sensitivity were assessed by using the following indices [9]: Homeostatic model assessment of pancreatic β-cell function (HOMA-β) =[(basal insulin [pM]×0.48)/(basal glucose [mM]-3.5)]; HOMA-IR=[(basal insulin [pM] × glucose [mM]) / 156.3]; C-peptide increment (ΔC-peptide=[stimulated C-peptide (pmol/mL)-basal C-peptide (pmol/mL)]; and insulin increment (Δinsulin=[stimulated insulin (pmol/L)-basal insulin (pmol/L)]. PCGR was defined as follows [10]: [(stimulated C-peptide [ng/mL]/stimulated glucose [mg/dL])×100]. The eGFR was derived from the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine-based equation [11].…”
Section: Methodsmentioning
confidence: 99%
“…Pancreatic β-cell function and insulin sensitivity were assessed using the following indices [ 16 ] : homeostasis model assessment (HOMA)-β = ([basal insulin (pmol/L) × 3.33]/[basal glucose (mmol/L) − 3.5]), homeostasis model assessment of insulin resistance = ([basal insulin (pmol/L) × basal glucose (mmol/L)]/135), C-peptide increment (ΔC-peptide = [stimulated C-peptide (nmol/L) − basal C-peptide (nmol/L)]), and insulin increment (Δinsulin = [stimulated insulin (pmol/L) − basal insulin (pmol/L)]). Postprandial C-peptide-to-glucose ratio (PCGR) was defined as follows [ 17 ] : (stimulated C-peptide [ng/mL]/stimulated glucose [mg/dL]) × 100. The eGFR was derived from the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation and also from the Modification of Diet in Renal Disease (MDRD) equation for the Korean population.…”
Section: Methodsmentioning
confidence: 99%
“…CPI is formed by dividing the C-peptide level into fasting blood glucose (Lee et al 2014). In many studies, CPI has been found to be more closely associated with beta cell function, insulin requirement, and microvascular complications (Saisho et al 2013;Lee et al 2014;Saisho 2016;Bando et al 2018). In our study, we could not demonstrate that CPI is used to predict proteinuria in anemic patients.…”
Section: Discussionmentioning
confidence: 99%